2016
DOI: 10.3390/ma9121019
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Soil-Water Characteristic Curves in Multiple-Cycles Using Membrane and TDR System

Abstract: The objective of this study is to estimate multiple-cycles of the soil-water characteristic curve (SWCC) using an innovative volumetric pressure plate extractor (VPPE), which is incorporated with a membrane and time domain reflectometry (TDR). The pressure cell includes the membrane to reduce the experimental time and the TDR probe to automatically estimate the volumetric water content. For the estimation of SWCC using the VPPE system, four specimens with different grain size and void ratio are prepared. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Alternatively, time domain reflectometry (TDR) based on the propagation velocity of electromagnetic waves has also been employed over the past few decades to estimate the water content [10]. Based on the difference between the dielectric constants of water (k water = 80) and other soil constituents (k air = 1, k solid = 3~7), a calibration relationship between the volumetric water content and the dielectric constant proposed by Topp et al [11] has been used [12][13][14][15][16][17][18][19]. Even for frozen soils, the volumetric water content can be easily estimated due to the low value of the dielectric constants of ice (k ice = 3.2) when compared to that of water.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, time domain reflectometry (TDR) based on the propagation velocity of electromagnetic waves has also been employed over the past few decades to estimate the water content [10]. Based on the difference between the dielectric constants of water (k water = 80) and other soil constituents (k air = 1, k solid = 3~7), a calibration relationship between the volumetric water content and the dielectric constant proposed by Topp et al [11] has been used [12][13][14][15][16][17][18][19]. Even for frozen soils, the volumetric water content can be easily estimated due to the low value of the dielectric constants of ice (k ice = 3.2) when compared to that of water.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the relationship between the volumetric water content and relative permittivity can be expressed by a cubic polynomial equation [ 15 , 23 , 24 ]. In addition, as the relative permittivities of dry soils and ice are similar, this relationship has been used to estimate the unfrozen water content of frozen soils [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of water from soil is usually estimated by using the soil-water characterization curve (SWCC) defined as the relationship between matric suction and the water content [1]. The matric suction represents the difference between pore-air and pore-water pressures which offer information about the amount of water and the energy state in liquid phase.…”
Section: Introductionmentioning
confidence: 99%